Identifying the ideal weekly training load for in-game performance in an elite Brazilian soccer team - Branquinho, L.; de França, E.; Teixeira, J. E.; Titton, A.; Leite de Barros, L. F.; Campos, P.; Marinho, D. A.; Forte, P.; Caperuto, E. C.; Thomatieli dos Santos, R. V.; Ferraz, R. (Frontiers in Physiology, 2024)
Introduction The purpose of this study was to investigate the ideal training load to be applied during periods of fixture congestion to ensure an adequate dose-response effect for performance maintenance.